2018
DOI: 10.2519/jospt.2018.7794
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Differences During Single-Leg Step-Down Between Individuals With Femoroacetabular Impingement Syndrome and Individuals Without Hip Pain

Abstract: Study Design Controlled laboratory study, case-control design. Background Despite recognition that femoroacetabular impingement syndrome (FAIS) is a movement-related disorder, few studies have examined dynamic unilateral tasks in individuals with FAIS. Objectives To determine whether movements of the pelvis and lower extremities in individuals with FAIS differ from those in individuals without hip pain during a single-leg step-down, and to analyze kinematic differences between male and female participants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…Recently, a rationale has been proposed that explains how exercise therapy aimed at improving the neuromuscular function of the hip, trunk and lower limbs might be effective for the non-surgical management of FAIS (10). Dynamic hip instability due to hip muscle weakness (11,12) and impaired pelvic control (13)(14)(15) may lead to exaggerated mechanical loading of the acetabular labrum (16), and upregulation of its nociceptive receptors (17). Therefore, it was suggested that improving the dynamic stability of the femoroacetabular joint through exercise therapy aimed at improving hip muscle strength and pelvis control during functional tasks (14), may reduce the mechanical loading and contact stress on the joint structures, and in turn downregulate nociceptor activity (10).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a rationale has been proposed that explains how exercise therapy aimed at improving the neuromuscular function of the hip, trunk and lower limbs might be effective for the non-surgical management of FAIS (10). Dynamic hip instability due to hip muscle weakness (11,12) and impaired pelvic control (13)(14)(15) may lead to exaggerated mechanical loading of the acetabular labrum (16), and upregulation of its nociceptive receptors (17). Therefore, it was suggested that improving the dynamic stability of the femoroacetabular joint through exercise therapy aimed at improving hip muscle strength and pelvis control during functional tasks (14), may reduce the mechanical loading and contact stress on the joint structures, and in turn downregulate nociceptor activity (10).…”
Section: Accepted Articlementioning
confidence: 99%
“…In addition, the small sample size did not allow us to use sex as a main factor in our analyses. Future larger studies should however consider sex-differences for exercise therapy effectiveness due to different clinical (33) and functional characteristics (13,34) presented by female and male patients with FAIS.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…control of the hip (Videos 32-34). 45 Women typically demonstrate greater hip flexion in both resisted side stepping with an elastic resistance band and the forward step-down, 44,45 which could further exaggerate symptoms, especially if anterior pelvic tilt is also increased. 44 Clinicians should monitor pelvic control during the advance to dynamic activities.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…The benchmark criteria were developed to challenge the hip and lower limb to exaggerate the movement compensations for an active population, possibly indicating hip and/or lower limb dysfunction. 32 , 55 , 59 , 72 , 103 For example, movement disorders exist in people with FAIS, showing smaller squat depth 55 and reduced posterior pelvic tilt, 8 , 57 ipsilateral trunk lean and pelvic rise towards the symptomatic hip, 33 greater hip flexion and anterior pelvic tilt 60 and greater peak trunk flexion angles. 46 Also, patellofemoral pain (PFP) has been associated with an increased peak hip adduction, internal rotation, contralateral pelvic drop and dynamic valgus index.…”
Section: Development and Description Of The Hllms Toolmentioning
confidence: 99%